Fertility of female goats across the seasons in Kerala - KUTTY, C IBRAHEEM (The Indian Journal of Animal Reproduction, 2023)
Goats in temperate climate are seasonal breeders and in tropics seasonality of reproduction is believed to be less.The study was carried out at Kerala Aaricultural University goat farm to find out fertility of remale goats across variousseasons and its relationship with climate variables so as to make suitable management alterations. Fenility obtained interms of 45,. day non return rate, conception rate and kids/kidding showed significant monthly and seasonal variations.However, number of oestrus detected showed no obvious relationship with success rate of AI in terms of non-return andconception rates. Also conception rate across months showed no relationship with any of the climatic variables studied. Itis concluded that even though fertility of female goats showed significant variations across months and seasons, there wasno influence ~f higher oestrus activity or any of the climatic variables across seasons.
Keywords: Season; fertility; conception; goats; artificial insemination